Neuroprotective Effect of Maternal Resveratrol Supplementation in a Rat Model of Neonatal Hypoxia-Ischemia - Dumont, Ursule; Sanchez, Stéphane; Repond, Cendrine; Beauvieux, Marie-Christine; Chateil, Jean-François; Pellerin, Luc; Bouzier-Sore, Anne-Karine; Roumes, Hélène (Frontiers in Neuroscience, 2021)
Neonatal hypoxia-ischemia (nHI) is a major cause of death or subsequent disabilities in infants. Hypoxia-ischemia causes brain lesions, which are induced by a strong reduction in oxygen and nutrient supply. Hypothermia is the only validated beneficial intervention, but not all newborns respond to it and today no pharmacological treatment exists. Among possible therapeutic agents to test, trans-resveratrol is an interesting candidate as it has been reported to exhibit neuroprotective effects in some neurodegenerative diseases. This experimental study aimed to investigate a possible neuroprotection by resveratrol in rat nHI, when administered to the pregnant rat female, at a nutritional dose. Several groups of pregnant female rats were studied in which resveratrol was added to drinking water either during the last week of pregnancy, the first week of lactation, or both. Then, 7-day old pups underwent a hypoxic-ischemic event. Pups were followed longitudinally, using both MRI and behavioral testing. Finally, a last group was studied in which breastfeeding females were supplemented one week with resveratrol just after the hypoxic-ischemic event of the pups (to test the curative rather than the preventive effect). To decipher the molecular mechanisms of this neuroprotection, RT-qPCR and Western blots were also performed on pup brain samples. Data clearly indicated that when pregnant and/or breastfeeding females were supplemented with resveratrol, hypoxic-ischemic offspring brain lesions were significantly reduced. Moreover, maternal resveratrol supplementation allowed to reverse sensorimotor and cognitive deficits caused by the insult. The best recoveries were observed when resveratrol was administered during both gestation and lactation (2 weeks before the hypoxic-ischemic event in pups). Furthermore, neuroprotection was also observed in the curative group, but only at the latest stages examined. Our hypothesis is that resveratrol, in addition to the well-known neuroprotective benefits via the sirtuin’s pathway (antioxidant properties, inhibition of apoptosis), has an impact on brain metabolism, and more specifically on the astrocyte-neuron lactate shuttle (ANLS) as suggested by RT-qPCR and Western blot data, that contributes to the neuroprotective effects.